Exposure to indoor combustion and adult asthma outcomes: environmental tobacco smoke, gas stoves, and woodsmoke. Issue 11 (1st November 2002) - Eisner, M D; Yelin, E H; Katz, P P; Earnest, G; Blanc, P D
Abstract : Background: Because they have chronic airway inflammation, adults with asthma may be particularly susceptible to indoor air pollution. Despite widespread exposure to environmental tobacco smoke (ETS), gas stoves, and woodsmoke, the impact of these exposures on adult asthma has not been well characterised. Methods: Data were used from a prospective cohort study of 349 adults with asthma who underwent structured telephone interviews at baseline and 18 month follow up. The prospective impact of ETS, gas stove, and woodsmoke exposure on health outcomes was examined. Results: ETS exposure at baseline interview was associated with impaired health status at longitudinal follow up. Compared with respondents with no baseline self-reported exposure to ETS, higher level exposure (≥7 hours/week) was associated with worse severity of asthma scores at follow up, controlling for baseline asthma severity, age, sex, race, income, and educational attainment (mean score increment 1.5 points; 95% CI 0.4 to 2.6). Higher level baseline exposure to ETS was also related to poorer physical health status (mean decrement –4.9 points; 95% CI –8.4 to –1.3) and asthma specific quality of life (mean increase 4.4 points; 95% CI –0.2 to 9.0) at longitudinal follow up. Higher level baseline ETS exposure was associated with a greater risk of emergency department visits (OR 3.4; 95% CI 1.1 to 10.3) and hospital admissions for asthma at prospective follow up (OR 12.2; 95% CI 1.5 to 102). There was no clear relationship between gas stove use or woodstove exposure and asthma health outcomes. Conclusion: Although gas stove and woodstove exposure do not appear negatively to affect adults with asthma, ETS is associated with a clear impairment in health status.